2022
DOI: 10.3389/fimmu.2022.746360
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine TGFβ Gene Polymorphism in Asthma: TGF-Related SNP Analysis Enhances the Prediction of Disease Diagnosis (A Case-Control Study With Multivariable Data-Mining Model Development)

Abstract: IntroductionTGF-β and its receptors play a crucial role in asthma pathogenesis and bronchial remodeling in the course of the disease. TGF-β1, TGF-β2, and TGF-β3 isoforms are responsible for chronic inflammation, bronchial hyperreactivity, myofibroblast activation, fibrosis, bronchial remodeling, and change the expression of approximately 1000 genes in asthma. TGF-β SNPs are associated with the elevated plasma level of TGF-β1, an increased level of total IgE, and an increased risk of remodeling of bronchi.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The transforming growth factor-β (TGF-β) has attracted the attention of researchers because of its pleiotropism and widespread occurrence in the body, including the airways. Despite single reports casting doubt on the role of TGF-β on airway remodeling processes, a vast majority of papers show a markedly increased expression of speci c TGF-β isoforms among asthmatic patients (8,11,(19)(20)(21)(22)(23). In our previous study, we proved that TGF-β1 and TGF-β2 isoform levels were statistically signi cantly higher among asthmatics compared to healthy volunteers.…”
Section: Discussionmentioning
confidence: 65%
“…The transforming growth factor-β (TGF-β) has attracted the attention of researchers because of its pleiotropism and widespread occurrence in the body, including the airways. Despite single reports casting doubt on the role of TGF-β on airway remodeling processes, a vast majority of papers show a markedly increased expression of speci c TGF-β isoforms among asthmatic patients (8,11,(19)(20)(21)(22)(23). In our previous study, we proved that TGF-β1 and TGF-β2 isoform levels were statistically signi cantly higher among asthmatics compared to healthy volunteers.…”
Section: Discussionmentioning
confidence: 65%
“…The complex thus formed leads to the phosphorylation of the kinase domain of TGFβRI, which in turn results in the activation of the Smad pathway. [9][10][11] This is therefore a targeted pathway for research into Analyses of the functional role of selected TGF-β cytokine homologous molecules conducted so far as part of the pilot study have demonstrated that newly designed peptide inhibitors for the region I inhibit gene expression of Smad-dependent and Smad-independent pathways, which indicates that they are potent to block the TGFβRI/ TGFβRII receptor complex in vitro (Figures 7 and 8, Tables 2-5).…”
Section: Discussionmentioning
confidence: 99%
“…The complex thus created is responsible This process may also take place via non-Smad pathways, in which the Erk1/2, Jun N-terminal kinase (JNK) and p38 MAP kinase pathways, Src tyrosine kinase, phosphatidylinositol 3 0 -kinase, and Rho GTPases are also involved. [3][4][5][6][7][8][9] Hyperactivity of TGF-β-Smad pathway by specific TGFβRI/ TGFβRII receptors (two highly conserved single transmembrane receptors with intracellular serine/threonine kinase domains) leads to the development of chronic pathway inflammation and miofibroblast activation. Therefore, the inhibition of TGFβRI (also known as activin receptor-like kinase 5, Alk5) seems to be a good strategy for the treatment of many abovementioned disorders manifesting with fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations